2014
DOI: 10.1007/s12015-014-9505-4
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Patterns of X Chromosome Inactivation in a New Line of Human Embryonic Stem Cells Established in Physiological Oxygen Concentrations

Abstract: One of the differences between murine and human embryonic stem cells (ESCs) is the epigenetic state of the X chromosomes in female lines. Murine ESCs (mESCs) present two transcriptionally active Xs that will undergo the dosage compensation process of XCI upon differentiation, whereas most human ESCs (hESCs) spontaneously inactivate one X while keeping their pluripotency. Whether this reflects differences in embryonic development of mice and humans, or distinct culture requirements for the two kinds of pluripot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
4
3
0
Order By: Relevance
“…2 ; Source Data file). These results led us to conclude that culturing primed pluripotent hESCs in atmospheric vs. physiological O 2 concentration does not alter the loss of XIST RNA expression and coating in hESCs, in agreement with other reports 29 , 35 , 43 , 45 , 68 70 . Furthermore, some X-linked genes become derepressed when XIST RNA is lost in cultured hESCs, also in agreement with previously published results 31 , 34 , 35 , 38 , 42 , 43 , 58 .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…2 ; Source Data file). These results led us to conclude that culturing primed pluripotent hESCs in atmospheric vs. physiological O 2 concentration does not alter the loss of XIST RNA expression and coating in hESCs, in agreement with other reports 29 , 35 , 43 , 45 , 68 70 . Furthermore, some X-linked genes become derepressed when XIST RNA is lost in cultured hESCs, also in agreement with previously published results 31 , 34 , 35 , 38 , 42 , 43 , 58 .…”
Section: Resultssupporting
confidence: 92%
“…Much prior work has demonstrated that prolonged culture of female hPSCs results in loss of XIST RNA coating and erosion of X-inactivation 29 , 31 , 35 , 36 , 38 , 39 , 42 , 43 , 45 , 57 , 59 . Consistent with previous findings, our data rule out atmospheric O 2 concentration as a cause of XIST RNA loss in hESCs 35 , 43 , 45 , 68 70 . Instead, we found that a primary source of XIST RNA loss in hESCs is the composition of the hESC culture medium.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…From these, despite its complex aneuploidy, only embryo 1 gave rise to a new line of hESC, named BR-6 ( Fig 1 ). This rate of derivation, although relatively low, was similar to those obtained by our group with euploid embryos [ 24 , 25 ].…”
Section: Resultssupporting
confidence: 90%
“…This allows the conclusion that X-inactivation in genotypically female ES cells of the common marmoset monkey occurs in a XIST -dependent manner. However, X inactivation does not seem to be an essential inherent characteristic for pluripotency in vitro 66 . Our data suggest that marmoset ES cells, with regard to X-inactivation, in general rather resemble human than mouse ES cells.…”
Section: Discussionmentioning
confidence: 99%